2016
DOI: 10.2146/ajhp150225
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a pharmacist–hospitalist collaborative model of inpatient care with multidisciplinary rounds in achieving quality measures

Abstract: Systematic implementation of either the PHC or the MDR model of care was associated with a decreased mean hospital LOS relative to LOS values with usual care only. No significant differences in readmissions at 30, 60, and 90 days were attributable to implementation of the PHC or the MDR model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…Of these, four studies of 3212 patients (n = 12; 33%) reported a statistically significant positive effect , and one study of 199 patients (n = 12; 8%) reported a negative result . Considering only LOS of index admission, three studies of 3171 patients (n = 12; 25%) showed a positive effect reducing LOS on average by 1.4 days . One study of 833 patients (n = 2; 50%) reported a reduction in LOS of the first readmission within 12 months after index admission .…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Of these, four studies of 3212 patients (n = 12; 33%) reported a statistically significant positive effect , and one study of 199 patients (n = 12; 8%) reported a negative result . Considering only LOS of index admission, three studies of 3171 patients (n = 12; 25%) showed a positive effect reducing LOS on average by 1.4 days . One study of 833 patients (n = 2; 50%) reported a reduction in LOS of the first readmission within 12 months after index admission .…”
Section: Resultsmentioning
confidence: 97%
“…. In total, 11,896 publications were imported, 544 full texts were read, and 28 publications were included in the analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations